A Forgotten Chiral Spiro Compound Revisited: 3, 3'‐Dimethyl‐3H, 3'H‐2, 2'‐spirobi[[1, 3]benzothiazole]. Issue 10 (25th August 2015) - Lindamulage De Silva, Angélique; Risso, Vesna; Jean, Marion; Giorgi, Michel; Monnier, Valérie; Naubron, Jean‐Valère; Vanthuyne, Nicolas; Farran, Daniel; Roussel, Christian
Abstract The title compound was obtained as a side product during dimerization‐oxidation steps of the carbene generated from N‐methylbenzothiazolium iodide. Chromatography on (S, S)‐Whelk O1 column showed on cooling a typical plateau shape chromatogram indicating an exchange between two enantiomers on the column. The thermal barrier to racemization was determined (85 kJ.mol−1 at 10 °C) by dynamic high‐performance liquid chromatography (DHPLC).The absolute configuration of the first (M) and second eluted (P) enantiomers on the (S, S)‐Whelk O1 column was established by comparing the reconstructed circular dichroism (CD) spectra from the CD detector signal and the calculated CD spectrum of the (P) enantiomer. Mass spectrometry revealed that 3, 3'‐dimethyl‐3H, 3'H‐2, 2'‐spirobi[[1, 3]benzothiazole] can be viewed as a masked thiophenate attached to a benzothiazolium framework. Chirality 27:716–721, 2015. © 2015 Wiley Periodicals, Inc.